2022
DOI: 10.1021/acsami.2c10005
|View full text |Cite
|
Sign up to set email alerts
|

Caught while Dissolving: Revealing the Interfacial Solvation of the Mg2+ Ions on the MgO Surface

Abstract: Interfaces between water and materials are ubiquitous and are crucial in materials sciences and in biology, where investigating the interaction of water with the surface under ambient conditions is key to shedding light on the main processes occurring at the interface. Magnesium oxide is a popular model system to study the metal oxide–water interface, where, for sufficient water loadings, theoretical models have suggested that reconstructed surfaces involving hydrated Mg2+ metal ions may be energetically favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Notably, the NEXAFS spectrum of the intermediate Mg 2+ species is markedly different from the XAS spectrum assigned to a fully dissolved octahedral Mg 2+ ion. 22,47 The body of evidence we have presented suggests that an interaction between the surface Mg 2+ ions and the water vapor molecules is established while excluding the occurrence of a surface dissolution process.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Notably, the NEXAFS spectrum of the intermediate Mg 2+ species is markedly different from the XAS spectrum assigned to a fully dissolved octahedral Mg 2+ ion. 22,47 The body of evidence we have presented suggests that an interaction between the surface Mg 2+ ions and the water vapor molecules is established while excluding the occurrence of a surface dissolution process.…”
Section: Resultsmentioning
confidence: 90%
“…Notably, while performing a similar AP-NEXAFS experiment to investigate the water/MgO interface, we recently observed that the water/MgO interaction is entirely reversed after treating the MgO sample up to 525 K for about 20−30 min. 22 Conversely, the fact that in our experimental conditions the water vapor/MgCl 2 interaction is not fully reversed after ca. 70 min of thermal treatment may be ascribed to the significantly different MgCl 2 surface properties if compared to those of MgO, e.g., to the higher higroscopicity of the MgCl 2 material.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations